Global Research Trends and Hotspots Analysis of the Scientific Production of Amitriptyline: A Bibliometric Approach - Cristian dos Santos Pereira; Jorddy Neves Cruz; Maria Karolina Martins Ferreira; Daiane Claydes Baia-; Eneas Andrade Fontes-Junior; Rafael Rodrigues Lima (MDPI AG, 2023)
Amitriptyline was first introduced as a medication to treat depression. Over time, this substance has been used to treat other conditions, such as gastrointestinal disorders, fibromyalgia, neuropathic pain, and analgesia, among others. However, there are no published studies that provide a broad view of the possible motivations that have led to changes in the use of amitriptyline. In this study, we have identified the landscape of use for amitriptyline based on knowledge mapping of the 100 most-cited articles about this drug. We searched Web of Science Core Collection without time and language restrictions. We obtained 14,446 results, but we only used the 100 most-cited articles that had amitriptyline as the object of study. We collected the following information from each article: authors, country of the corresponding authors, year of publication, citation count, citation density (number of citations per year), and keywords. In addition, we seek to map in the chosen articles study design and research findings. We found that since 1980, the use of amitriptyline has expanded beyond depression, moving to off-label use to treat a variety of diseases and conditions, including post-herpetic neuralgia, neuropathic pain, primary fibrosis, fibromyalgia, and migraine, can be considered a drug with more clinical applicability than its original clinical indication.